METHODOLOGICAL BASES OF THE GEOECONOMIC DEVELOPMENT STRATEGY OF THE NORTH-CAUCASIAN MACRO-REGION - O. Ishchenko-Padukova; I. Movchan (Вестник Северо-Кавказского федерального университета)
The article reveals the methodological foundations and the most important directions of the strategy of geoeconomic development of the subjects of the North Caucasian macroregion, defines the principles and priorities of strategic geoeconomic development. The geo-economic basis of the socio-economic growth of the regions of the North Caucasus is to increase the investment capacity of territorial development, develop innovative potential, increase the quota of small enterprises in the scope of innovative research and development.